Ochrona zamków oraz pałaców i dworów szlacheckich na Warmii i Mazurach – aspekty prawnokarne i kryminologiczne - Narodowska, Joanna; Duda, Maciej (Studia Prawnoustrojowe, 2019)
The authors of the paper disscuss the issues of conservation of the cultural heritage located in Warmia and Mazury region. Within the introductory issues, basic terms related to the subject matter are defined. The main part of consideration is devoted to description of the most valuable elements of the region’s material cultural heritage, such as castles, palaces and nobile manors. The particular attention is paid to presentation of pathological phenomena directed against monuments in the historical and contemporary perspective. A contrario the positive examples of revitalization of monuments of Warmia and Mazury are also pointed out. A dogmatic and legal analysis of the provisions of the law on conservation of monuments in the context of the destruction and damage of monuments are also made. The conclusions indicate the contemporary threats to the cultural heritage of the region and the possibilities of counteracting them.